Current Treatment Approaches to HCC with a Special Consideration to Transplantation - N. Bhardwaj; M. T. P. R. Perera; M. A. Silva (Journal of Transplantation)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer deaths worldwide. The mainstay of treatment of HCC has been both resectional and transplantation surgery. It is well known that, in selected, optimized patients, hepatectomy for HCC may be an option, even in patients with underlying cirrhosis. Resectable patients with early HCC and underlying liver disease are however increasingly being considered for transplantation because of potential for better disease-free survival and resolution of underlying liver disease, although this approach is limited by the availability of donor livers, especially in resectable patients. Outcomes following liver transplantation improved dramatically for patients with HCC following the implementation of the Milan criteria in the late 1990s. Ever since, the rather restrictive nature of the Milan criteria has been challenged with good outcomes. There has also been an increase in the donor pool with marginal donors including organs retrieved following cardiac death being used. Even so, patients still continue to die while waiting for a liver transplant. In order to reduce this attrition, bridging techniques and methods for downstaging disease have evolved. Additionally new techniques for organ preservation have increased the prospect of this potentially curative procedure being available for a greater number of patients.